1995
DOI: 10.1002/cyto.990220204
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of dna content in bladder cancer based on flow cytometric analysis of 249 transitional cell carcinomas

Abstract: The prognostic significance of DNA index (DI), S-phase fraction, and heterogeneity determined by flow cytometric DNA analysis was assessed in a prospective study of 249 newly diagnosed transitional cell carcinomas of the bladder. The median observation time was 4.8 years. A total of 456 subpopulations were detected. The S-phases could be estimated in 299 subpopulations. A DI > 1.25 or an S-phase above 9.7%were strongly correlated to invasiveness.One hundred and ten patients were treated with transurethral rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Whereas recent studies showed an association between DNA aneuploidy in the resected tumor tissue and progression to invasive cancer (17)(18)(19)(20), none had addressed the prognostic effect of DNA aneuploidy in cells obtained from bladder washings of an endoscopically normal organ. Conceivably, DNA aneuploidy in bladder washing may reflect the presence of T is in bladder mapping, which was not assessed in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas recent studies showed an association between DNA aneuploidy in the resected tumor tissue and progression to invasive cancer (17)(18)(19)(20), none had addressed the prognostic effect of DNA aneuploidy in cells obtained from bladder washings of an endoscopically normal organ. Conceivably, DNA aneuploidy in bladder washing may reflect the presence of T is in bladder mapping, which was not assessed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the trial at 12 and 36 months have previously been published (16). Importantly, recent studies have shown that DNA aneuploidy in papillary tumor tissue predicts the subsequent risk of invasive cancer (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…34 A FACScan flow cytometer was used (Becton Dickinson Immunocytometry Systems, San Jose, CA) and the DNA index (DI) was calculated. A tumor was denominated diploid (DI 5 1) when only one peak was detected and aneuploid when two (or more) separate peaks were found.…”
Section: Dna Histogram Analysismentioning
confidence: 99%
“…Furthermore, Vindelov et al [14]have shown that response to radiation therapy is better for patients whose superficial bladder cancers have lower S–phase values.…”
Section: Discussionmentioning
confidence: 99%
“…Several flow cytometric studies of superficial bladder cancer have found tumor proliferation to be a prognostically useful adjunct to DNA ploidy information [11, 12, 13, 14]. However, not all such studies have found significant survival differences between those whose tumors have low or high S–phase fractions [15].…”
Section: Introductionmentioning
confidence: 99%